Chapter 9. Words From Partner Societies. (April 2018) - Golden, Barbara; Stiris, Tom; Panés, Julián; Namazova-Baranova, Leyla; Van Gossum, André; Boeing, Heiner; Bhutta, Zulfiqar A.; Madrazo, Armando; Heubi, James E.; Mouane, Nezha; Fockens, Paul; Koletzko, Berthold
Abstract : ABSTRACT: On the occasion of the 50th anniversary of the European Society of Paediatric Gastroenterology, Hepatology and Nutrition (ESPGHAN), its close partner associations submitted comments and felicitations which are presented here. These include words from the Latin American (LASPGHAN), North American (NASPGHAN) and Panarabian Societies (PASPGHAN) and the Commonwealth Association (CAPGHAN) of Paediatric Gastroenterology, Hepatology and Nutrition, the Federation of International Societies of Paediatric Gastroenterology, Hepatology and Nutrition (FISPGHAN), the European Academy of Pediatrics (EAP), the European Pediatric Association/Union of National Pediatric Societies (EPA-UNEPSA), the International Pediatric Association (IPA), the European Crohn's and Colitis Organisation (ECCO), European Society for Clinical Nutrition and Metabolism (ESPEN), the Federation of European Nutrition Societies (FENS), and United European Gastroenterology (UEG).